Identity and territory: Jewish perceptions of space in antiquity - Ben-Eliyahu, Eyal (University of California Press, 2019)
Frontmatter -- Contents -- Illustrations -- Preface -- Introduction -- 1. From Judah to Israel: Territory and Identity -- 2. Borders, Space, and Identity in Second Temple Literature -- 3. From Earthly Land to Holy Land -- 4. Land of the Sages -- 5. Rabbinic Literature Confronts Nonrabbinic Jewish Culture and Christianity: The Question of Holy Spaces -- Conclusion -- Bibliography -- Index of Places -- Index of Sources -- Index of Persons -- Index of Subjects